The Scanian Economic Demographic Database (SEDD) - Dribe, Martin; Svensson, Patrick; Bengtsson, Tommy (Lund University, 2021)
The Scanian Economic Demographic Database (SEDD) is based on family reconstitutions for nine rural parishes (Ekeby, Frillestad, Halmstad, Hässlunda, Hög, Kågeröd, Kävlinge, Sireköpinge and Stenestad) and one city (Helsingborg) in Scania, the southernmost county of Sweden, in which information in church records on births, deaths and marriages are linked together to form families. The database is the result of project collaborations between the Centre for Economic Demography (CED) and the Regional Archives in Lund. The co-operation has produced both an event database, in which all basic source material is registered, and an applied research database. The event database is accessible through the Regional Archives in Lund.

The description that follows primarily relates to the research database which contains information on five parishes (Halmstad, Hög, Kågeröd, Kävlinge and Sireköpinge). From the late 19th century onwards, one of the rural parishes was transformed from a minor rural village to a small industrial town (Kävlinge), while the others preserved their rural characters.

At its present stage, the research database includes data for 104 000 individuals from 1646 up to 1968, to which data from central registers for the period up to 2011 has been added. Data for the city of Landskrona are presently digitized. The database contains a variety of information on individual as well as household/family level and each individual in the database is under observation from birth/ in-migration and throughout the life span/ until an out-migration occurs. The fact that the database covers almost four centuries and that it combines economic and demographic data in one database has made it unique by Swedish comparisons.

Demographic variables include:

Births
Deaths
Cause of death
Marriages
In-migration
Out-migration
Birth-order


Socioeconomic and health variables include:

Occupation
Land holdings (farm size etc.)
Type of residence (farm, croft, cottage etc.)
Property ownership (freehold, crown, noble)
Income
Height
Health at birth
Health at mustering

Household variables include:

House-hold size
Typology of house-hold members (servants, nuclear family, lodgers etc.)

Purpose:

The purpose of the Scanian Economic Demographic Database (SEDD) is to function as a research infrastructure for economic as well as demographic research.

Skånes ekonomisk-demografiska databas (SEDD) innehåller demografiska och socioekonomiska data från 1600-talet till idag. Informationen är hämtad ifrån nio stycken rurala socknar i Skåne (Ekeby, Frillestad, Halmstad, Hässlunda, Hög, Kågeröd, Kävlinge, Sireköpinge och Stenestad) samt från en tätort (Helsingborg), där kyrkböckernas uppgifter om individers födslar, dödsfall och giftermål länkats samman för att rekonstruera familjer och familjeförhållanden. Databasen är resultatet av ett samarbetsprojekt mellan Landsarkivet i Lund och Centrum för Ekonomisk Demografi vid Lunds universitet. Samarbetet har resulterat i en händelsedatabas (tillgänglig via Landsarkivet) och en forskningsdatabas. Beskrivningen nedan rör forskningsdatabasen som innehåller fem församlingar i Skåne: Halmstad, Hög, Kågeröd, Kävlinge och Sireköpinge.

I dagsläget innehåller forskningsdatabasen data för 104 000 individer från 1646 fram till år 1968, som kompletterats med information från SCB för perioden fram till 2011. Individer följs från födsel eller inflyttning till död eller utflyttning. För närvarande excerperas även data för Landskrona under 1900-talet. Att det är en så pass heltäckande databas, samt att den kombinerar demografiska och socioekonomiska uppgifter, medför att SEDD är unik i Sverige.


De demografiska variablerna inkluderar:

Födslar
Dödsfall
Dödsorsaker
Giftermål
Inflyttning
Utflyttning
Födelseordning

De socioekonomiska och hälsorelaterade variablerna inkluderar:

Yrke
Jordinnehav
Bostadstyp
Äganderätt
Inkomst
Längd
Hälsa vid födsel
Hälsa vid mönstring
Till dessa finns hushållsvariabler såsom familjestorlek, position inom familjen etc.

Syfte:

Skånes ekonomisk-demografiska databas (SEDD) har som syfte att fungera som en forskningsinfrastruktur som kan tillgodose såväl den ekonomiska och demografiska forskningens som släkt- och hembygdsforskares behov.
Skånes ekonomisk-demografiska databas (SEDD)
Keywords: cultural history; kulturhistoria; economic history; ekonomisk historia; rural economics; landsbygdsekonomi; SwedPop; SwedPop; DEMOGRAPHY (POPULATION, VITAL STATISTICS, AND CENSUSES); DEMOGRAFI (POPULATION, VITALSTATISTIK OCH FOLKRÄKNINGAR); Income, property and investment/saving; Inkomster, egendom och investeringar/sparande; HEALTH; HÄLSA; HISTORY; HISTORIA; Other Agricultural Sciences not elsewhere specified; Övrig annan lantbruksvetenskap; Social Sciences; Samhällsvetenskap; Economic History; Ekonomisk historia